2016
DOI: 10.5993/ajhb.40.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs of Marshallese Regarding Type 2 Diabetes

Abstract: Objectives The Marshallese population suffers from disproportionate rates of type 2 diabetes. This study identifies the underlying beliefs and perceptions that affect diabetes self-management behavior among the US Marshallese population living in Arkansas. Methods The study uses qualitative focus groups with a semi-structured interview guide developed using a community-based participatory research (CBPR) approach and the Health Belief Model. Data was collected from a total of N = 41 participants and bilingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 32 publications
(47 reference statements)
1
45
0
Order By: Relevance
“…The Marshallese stakeholders also explained that any changes to eating habits and behavior must be focused on the family unit in order to be effective, and stakeholders reinforced that incorporating collectivist and family-centered concepts into the DSME curriculum and delivery method was imperative. Stakeholders recommended that DSME be implemented within an extended family model so additional family members could benefit and the patient with diabetes would be supported by their family members (Hallgren et al, 2015; McElfish et al., 2016). Stakeholders continue to work side by side with researchers to culturally adapt DSME for implementation in a family model (McElfish, Bridges, et al, 2015).…”
Section: Process and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Marshallese stakeholders also explained that any changes to eating habits and behavior must be focused on the family unit in order to be effective, and stakeholders reinforced that incorporating collectivist and family-centered concepts into the DSME curriculum and delivery method was imperative. Stakeholders recommended that DSME be implemented within an extended family model so additional family members could benefit and the patient with diabetes would be supported by their family members (Hallgren et al, 2015; McElfish et al., 2016). Stakeholders continue to work side by side with researchers to culturally adapt DSME for implementation in a family model (McElfish, Bridges, et al, 2015).…”
Section: Process and Resultsmentioning
confidence: 99%
“…Although patient stakeholders have only wanted limited involvement in the quantitative analysis, they have been more intensively involved in the qualitative data analysis (Hallgren et al, 2015; McElfish et al, 2016). Community co-investigators have shown significant interest and ownership in how the data is interpreted and disseminated.…”
Section: Process and Resultsmentioning
confidence: 99%
“…Arkansas has the largest population of Marshallese in the continental US with a population of 12,000 persons. (3,(6)(7)(8)(9)(10) This growth is primarily focused in Springdale, Arkansas and has been perpetuated by employment in the poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…UAMS used a community-based participatory approach to work with the Marshallese community in Arkansas to identify and address community health concerns. (6,24,(27)(28)(29) Marshallese community members identified faith-based organizations (FBOs) as important to their culture and recommended that we work closely with FBOs. Stakeholders stated that virtually all Marshallese attend at least one FBO on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation